Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Of course! Let's solve the given equation step-by-step. The equation is:
[tex]\[ 16x - [3x - (6 - 9x)] = 30x + [(3x + 2) - (x + 3)] \][/tex]
### Step 1: Simplify inside the brackets
1. Simplify inside the first bracket:
[tex]\[ 3x - (6 - 9x) \][/tex]
Distribute the negative sign inside the bracket:
[tex]\[ 3x - 6 + 9x = 12x - 6 \][/tex]
2. Simplify inside the second bracket:
[tex]\[ (3x + 2) - (x + 3) \][/tex]
Distribute the negative sign inside the bracket:
[tex]\[ 3x + 2 - x - 3 = 2x - 1 \][/tex]
### Step 2: Substitute the simplified expressions back into the equation
[tex]\[ 16x - (12x - 6) = 30x + (2x - 1) \][/tex]
### Step 3: Simplify the equation further
1. On the left-hand side:
[tex]\[ 16x - 12x + 6 = 4x + 6 \][/tex]
2. On the right-hand side:
[tex]\[ 30x + 2x - 1 = 32x - 1 \][/tex]
So the equation now looks like:
[tex]\[ 4x + 6 = 32x - 1 \][/tex]
### Step 4: Isolate the variable [tex]\( x \)[/tex]
1. Move all terms containing [tex]\( x \)[/tex] to one side and constant terms to the other side:
[tex]\[ 4x + 6 = 32x - 1 \][/tex]
Subtract [tex]\( 4x \)[/tex] from both sides:
[tex]\[ 6 = 28x - 1 \][/tex]
2. Add 1 to both sides:
[tex]\[ 7 = 28x \][/tex]
3. Divide both sides by 28 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{7}{28} \][/tex]
### Step 5: Simplify the fraction
[tex]\[ \frac{7}{28} = \frac{1}{4} \][/tex]
Therefore, the solution to the equation is:
[tex]\[ x = \frac{1}{4} \][/tex]
[tex]\[ 16x - [3x - (6 - 9x)] = 30x + [(3x + 2) - (x + 3)] \][/tex]
### Step 1: Simplify inside the brackets
1. Simplify inside the first bracket:
[tex]\[ 3x - (6 - 9x) \][/tex]
Distribute the negative sign inside the bracket:
[tex]\[ 3x - 6 + 9x = 12x - 6 \][/tex]
2. Simplify inside the second bracket:
[tex]\[ (3x + 2) - (x + 3) \][/tex]
Distribute the negative sign inside the bracket:
[tex]\[ 3x + 2 - x - 3 = 2x - 1 \][/tex]
### Step 2: Substitute the simplified expressions back into the equation
[tex]\[ 16x - (12x - 6) = 30x + (2x - 1) \][/tex]
### Step 3: Simplify the equation further
1. On the left-hand side:
[tex]\[ 16x - 12x + 6 = 4x + 6 \][/tex]
2. On the right-hand side:
[tex]\[ 30x + 2x - 1 = 32x - 1 \][/tex]
So the equation now looks like:
[tex]\[ 4x + 6 = 32x - 1 \][/tex]
### Step 4: Isolate the variable [tex]\( x \)[/tex]
1. Move all terms containing [tex]\( x \)[/tex] to one side and constant terms to the other side:
[tex]\[ 4x + 6 = 32x - 1 \][/tex]
Subtract [tex]\( 4x \)[/tex] from both sides:
[tex]\[ 6 = 28x - 1 \][/tex]
2. Add 1 to both sides:
[tex]\[ 7 = 28x \][/tex]
3. Divide both sides by 28 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{7}{28} \][/tex]
### Step 5: Simplify the fraction
[tex]\[ \frac{7}{28} = \frac{1}{4} \][/tex]
Therefore, the solution to the equation is:
[tex]\[ x = \frac{1}{4} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.